Does Fiscal Policy Tools have the Potential to Stimulate Performance of Manufacturing Sector in Nigeria? - Ubesie, Cyril Madubuko; Ananwude, Amalachukwu; Cyracus, Ezechi Nwanekpe; Emmanuel , Ebe (Finance & Economics Review, 2020)
Purpose: There is no denying the fact that the Nigerian manufacturing sector is not performing up to the expectation. The poor performance of the manufacturing sector is attributed largely to the poor state of basic infrastructures, especially power supply, and good road networks. To this end, this study examined the potential of fiscal policy to stimulate manufacturing sector performance in Nigeria. Methods: The model estimation employed the Ordinary Least Square (OLS) estimation technique, while the effect of estimation was carried out using the Granger causality test based on the data from the Central Bank of Nigeria (CBN) and Federal Inland Revenue Service (FIRS) for the period of 1986 to 2019. Results: The result of the analysis revealed that recurrent expenditure has no significant effect on manufacturing sector performance. However, capital expenditure, fiscal deficit, and the company’s income tax significantly affect manufacturing sector performance. Implications: The Federal, State, and Local governments should stop wasteful expenditure on unnecessary entertainment on meetings, seminars, workshops, foreign trips, etc. to increase spending on basic industrial infrastructures, most importantly on the power supply and road network to stimulate the manufacturing sector performance.